A cross‐sectional study of MRI features and the gut microbiome in pediatric‐onset multiple sclerosis - Feng Zhu; Yinshan Zhao; Douglas L. Arnold; Amit Bar‐Or; Charles N. Bernstein; Christine Bonner; Morag Graham; Janace Hart; Natalie Knox; Ruth Ann Marrie; Ali I. Mirza; Julia O'Mahony; et al. (Annals of Clinical and Translational Neurology, 2024)
Abstract Objective To identify gut microbiome features associated with MRI lesion burden in persons with pediatric‐onset multiple sclerosis (symptom onset <18 years). Methods A cross‐sectional study involving the Canadian Paediatric Demyelinating Disease Network study participants. Gut microbiome features (alpha diversity, phylum‐ and genus‐level taxa) were derived using 16S rRNA sequencing from stool samples. T1‐ and T2‐weighted lesion volumes were measured on brain MRI obtained within 6 months of stool sample procurement. Associations between the gut microbiota and MRI metrics (cube‐root‐transformed) were assessed using standard and Lasso regression models. Results Thirty‐four participants were included; mean ages at symptom onset and MRI were 15.1 and 19.0 years, respectively, and 79% were female. The T1‐ and T2‐weighted lesion volumes were not significantly associated with alpha diversity (age and sex‐adjusted p > 0.08). At the phylum level, high Tenericutes (relative abundance) was associated with higher T1 and T2 volumes (β coefficient = 0.25, 0.37) and high Firmicutes, Patescibacteria or Actinobacteria with lower lesion volumes (β coefficient = −0.30 to −0.07). At the genus level, high Ruminiclostridium, whereas low Coprococcus 3 and low Erysipelatoclostridium were associated with higher lesion volumes. Interpretation Our study characterized the gut microbiota features associated with MRI lesion burden in pediatric‐onset MS, shedding light onto possible pathophysiological mechanisms.